Analisis Tingkat Keramahan Lingkungan Alat Penangkapan Ikan Utama Di Desa Kota Bani, Bengkulu Utara - Zamdial Zamdial; Resyl V. Apriandini; Ali Mukqsit (Universitas Pattimura, 2023)
Environmentally friendly fishing gear is a fishing gears that does not have a negative impact on the environment, does not damage the bottom of the waters so that it can support the sustainable management of marine biological resources. This study aims to analyze of environmental friendliness level of the main fishing gears in the village of Bani City, Putri Hijau District, North Bengkulu Regency. The research was conducted using a survey method. Research data were collected by observation, interview and documentation methods. Data analysis was carried out by descriptively method. There are 2 fishing units operated by fishermen in Kota Bani Village, Putri Hijau District, North Bengkulu Regency, namely gillnets and bottom longlines. Based on the results of an analysis of the criteria for environmentally friendly fishing gear, both gill nets and bottom longlines, are included in the category of very environmentally friendly fishing gear, with respective scores of 29.4 and 29,0.